2018
DOI: 10.18203/2349-3933.ijam20183893
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the success rate of extra corporal shock wave lithotripsy (ESWL) in patients with urinary stones

Abstract: Background: Urinary stones are one of the most common and earliest known human diseases. Extracorporeal shock wave lithotripsy (ESWL) is known as the most common method for treating urinary stones less than 20-25 mm. The aim of this study was to evaluation the success rate of ESWL in patients with urinary stones.Methods: In this cross-sectional descriptive study 200 patients with urinary stones between 7-25 mm which were candidates for lithotripsy, enrolled in the study. Patients with coagulation disorders, ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…14 Moreover, the study showed that the likelihood of successfully removing stones decreases as their size increases.which is corroborated by other studies which have found larger stones to be more resistant and require higher energy waves and multiple sessions for successful removal. [17][18][19] Additionally, studies suggest that larger stone sizes lead to an increased risk of hematuria and pain. This is in line with previous studies showed that that stone size is the most influential factor in predicting ESWL outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Moreover, the study showed that the likelihood of successfully removing stones decreases as their size increases.which is corroborated by other studies which have found larger stones to be more resistant and require higher energy waves and multiple sessions for successful removal. [17][18][19] Additionally, studies suggest that larger stone sizes lead to an increased risk of hematuria and pain. This is in line with previous studies showed that that stone size is the most influential factor in predicting ESWL outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One recommended option is ESWL, which can be further improved by combining it with other treatments. 18 In a recent investigation by Cakiroglu et al 23 , shock wave lithotripsy (SWL) emerged as the preferred initial treatment for kidney stones, even those measuring less than 400mm in diameter. This is primarily due to SWL's non-invasive nature and its ability to effectively fragment stones into smaller pieces that can be passed through the urinary system.…”
Section: Discussionmentioning
confidence: 99%